Analysis of Meshing Temperature of Plastic Gear based on the Multi Heat Source of Frictional Heat Flux and Hysteresis Heat Flux - Guoda Yu; Huaiju Liu; Caichao Zhu; Zehua Lu; Peitang Wei (Jixie chuandong)
The meshing temperature of plastic gear affects the mechanical behaviors such as fatigue， wear and noise， which should not be ignored in the mechanical response and performance prediction of plastic gear. In order to predict the meshing temperature of plastic gears， a finite element numerical model of plastic gear temperature field is established considering the temperature-modulus effect of POM material and the multi-heat sources effect of frictional heat and hysteresis heat flux. Based on POM thermo-viscoelastic contact analysis， frictional heat flow and hysteresis loss heat flow are obtained as heat sources. Through the iterative calculation of the interaction between the steady meshing temperature and elastic modulus of plastic gear， the steady meshing temperature and tooth surface flash temperature are obtained. The steady meshing temperature results are in good agreement with the test results， and the flash temperature is in good agreement with the Blok theory. It is found that the temperature rise of hysteresis loss heat has little effect on the steady meshing temperature under dry condition， while the temperature rise caused by friction is the main component of the steady running temperature of plastic gear.